Eradication rate and treatment resistance for infection by helicobacter pylori in patients of the Hospital Apoyo-Pichanaki in the year 2018. - Leonardo Reyes, Edith Ysabel (2020)
Objective: To evaluate the rate of eradication and bacterial resistance to treatment for Helicobacter pylori infection in patients at the Apoyo-Pichanaki Hospital in the year 2018. Material and methods: It corresponds to a descriptive, retrospective and cross-sectional study, using a sample of 327 clinical histories of patients with Helicobacter pylori infection, from January to December 2018, using the document analysis technique and the instrument the data record. Results: The eradication rate for Helicobacter pylori infection in patients of the Apoyo- Pichanaki Hospital was 91.4%, with optimal first-line therapeutic regimen with clarithromycin 500 mg, amoxicillin 1g and omeprazole 20 mg every 12 hours for 14 days, the highest rate being eradication in females with 60.9% and only 39.1% in males. The highest bacterial resistance was 25% for ages 44 to 48 years and for females, 8.6% of bacterial resistance was found. Conclusions: It has been found an eradication rate for Helicobacter pylori of 91.4%, and 8.6% bacterial resistance to the first and second line of treatment used for the eradication of the infection.